Integrating Religious Moderation Values in an English Course Book - Andriani, Fenty; Puspitasari, Desi (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
This study aims to offer such an alternative to the lack of suitable materials that it addresses the need for comprehensive educational resources by focusing on the development of an English course book integrated with religious moderation indicators. The steps in this research were generally known as the R&D cycle developed by Borg and Gall. They were research and information collecting, planning, development of the preliminary form of the product, preliminary field test, main product revision, main field testing, operational product revision, operational field test, and final product revision. Throughout the research process, the course book is able to provide instructional sentences in English that serves as scaffolding talk for instructors who may not be accustomed to using English in the classroom. This approach fosters an active and dynamic English language environment, offering valuable language input for students. The content and learning experiences of all chapters are organized in such a way that they are integrated with religious moderation indicators covering national commitment, tolerance, rejecting of violence, and accommodating local culture. Each chapter of the course book consists of six parts, starting from let’s find out, let’s listen, let’s speak, let’s read, let’s write, and let’s evaluate. Overall, the English course book developed does not only encompass comprehensive English skills and language components but also align with the interests and needs of students while integrating values of religious moderation.